Postpartum practice: guidelines for clinical practice from the French College of Gynaecologists and Obstetricians (CNGOF). (July 2016) - Sénat, Marie-Victoire; Sentilhes, Loïc; Battut, Anne; Benhamou, Dan; Bydlowski, Sarah; Chantry, Anne; Deffieux, Xavier; Diers, Flore; Doret, Muriel; Ducroux-Schouwey, Chantal; Fuchs, Florent; Gascoin, Geraldine; et al.
Abstract: Objective: To make evidence-based recommendations for the postpartum management of women and their newborns, regardless of the mode of delivery. Material and methods: Systematic review of articles from the PubMed database and the Cochrane Library and of recommendations from the French and foreign societies or colleges of obstetricians. Results: Because breast-feeding is associated with reductions in neonatal, infantile, and childhood morbidity (lower frequency of cardiovascular, infectious, and atopic diseases and infantile obesity) (LE2) and improved cognitive development in children (LE2), exclusive and extended breastfeeding is recommended (grade B) for at least 4–6 months (professional consensus). Pharmacological treatments for inhibition of lactation should not be given routinely to women who do not wish to breastfeed (professional consensus). Because of potentially serious adverse effects, bromocriptine is contraindicated in inhibiting lactation (professional consensus). For women aware of the risks of pharmacological treatments to inhibit lactation but choose to take them, lisuride and cabergoline are the preferred drugs (professional consensus). Regardless of the mode of delivery, only women with bleeding or symptoms of anemia should be tested for it (professional consensus). Immediate postoperative monitoring after cesarean delivery should be performed in the postanesthesia care unit (PACU). An analgesic multimodal protocol for analgesia, preferring oral administration, should be developed by the medical team and be available for all staff (professional consensus) (grade B). Thromboprophylaxis with compression stockings should begin the morning of all cesarean deliveries and maintained for at least 7 postoperative days (professional consensus) with or without the addition of LMWH, depending on the presence and severity (major or minor) of additional risk factors. It is recommended that women be informed of the dangers of closely spaced pregnancies (LE3), that effective contraception begin no later than 21 days post partum for women who do not want such a pregnancy (grade B), and that it be prescribed at the maternity ward (professional consensus). In view of the postpartum risk of venous thromboembolism, use of combination hormonal contraception is not recommended before six weeks post partum (grade B). Pelvic floor rehabilitation in asymptomatic women to prevent urinary or anal incontinence in the medium or long term is not recommended (professional consensus). Rehabilitation using pelvic floor muscle contraction exercises is recommended to treat persistent urinary incontinence at 3 months post partum (grade A), regardless of the type of incontinence. Postpartum pelvic floor rehabilitation is recommended to treat anal incontinence (grade C), but not to treat or prevent prolapse (grade C) or dyspareunia (grade C). The months following the birth are a period of transition and of psychological changes for all parents (LE2) and are still more difficult for those with psychosocial risk factors (LE2). Situations of evident psychological difficulties can have a significant effect on the child's psychological and emotional development (LE3). Among these difficulties, postpartum depression is most common, but the risk of all mental disorders is generally higher in the perinatal period (LE3). Conclusion: The postpartum period presents clinicians with a unique and privileged opportunity to address the physical, psychological, social, and somatic health of women and babies.